FACTORS INFLUENCE THE LEVEL OF JOB SATISFACTION AMONG FRONT LINE EMPLOYEES IN PRIVATE HEALTHCARE-A CASE STUDY IN PUSRAWI HOSPITAL SDN. BHD. - Santi., Anadarao. (Universiti Malaysia Sarawak, UNIMAS, 2007)
The main purpose of this study is to investigate the influence of personal satisfaction, professional support, training, workload and team spirit on front line employees’ job satisfaction in private healthcare. This research also aims to measure the level of job satisfaction among front line employees in private healthcare and to identify the most influential factor affecting front line employees’ job satisfaction. This study differs from previous studies in two ways: in dealing with private healthcare and focuses specifically on front line employees.Hypotheses were constructed by reviewing a model proposed by Chou,Boldy and Lee in the area of employees’ job satisfaction. The model represents the expected relationships among five satisfaction components: personal satisfaction, workload, team spirit, training and professional support. A total of 46 front line employees at a Pusrawi Hospital,Kuala Lumpur completed self -administered questionnaire. By using Pearson correlation analysis,the relationship between the variables was measured and regression analysis was used to determine the dominant factor between the independent variables . The study found that the level of job satisfaction for 59 percent respondents is in the medium level. Findings of the study also indicate that professional support, workload and training influence the level of job satisfaction among frontline employees. This study proposes that personal satisfaction and team spirit do not influence front line employees’ job satisfaction. Empirical findings also suggest that the workload of employees appears to be the most influential factor affecting front line employees’ job satisfaction. It is suggested that to enhance the level of job satisfaction among front line employees, managers need to actively monitor workloads and build good relationship with them.These activities could assist in maintaining and increasing job satisfaction.